Performance analysis of a cascade controller for conventional and deregulated power systems. (3rd July 2020) - Acharyulu, B. V. S; Mohanty, Banaja; Hota, P. K.
ABSTRACT: A three unequal area interconnected power system under deregulated environment having multi-sources of generation is considered. The first area consists of solar thermal and thermal unit, the second area consists of thermal and hydro unit, and the third area contains thermal and gas units as generating units with proper generation rate constraint (GRC). Cascaded proportional integral-proportional derivative with filter coefficient (CPIPDF) is employed as a secondary controller. A recent meta-heuristic algorithm called moth flame optimization (MFO) is considered to optimize the controller parameters. System performances are compared with the classical controllers like proportional-integral (PI), proportional-integral-derivative (PID), proportional-integral-derivative with filter coefficient (PIDF) and cascaded proportional-integral-proportional-derivative (CPIPD) controller. MFO tuned CPIPDF controller performs better than all other controllers considered in this paper for different electrical transactions. Robustness of the optimum gains of CPIPDF controller obtained at poolco transaction condition is evaluated. In addition, system performance is studied with variation in disco participation matrix (DPM).